PENGEMBANGAN KONSEP JASA PENDIDIKAN TINGGI BERBASIS KEINGINAN KONSUMEN POTENSIAL - Andriya Risdwiyanto; Basu Swastha Dharmmesta (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
This research tests a model of the influence of marketing stimuli to the choice of private colleges in Yogyakarta and Central Java. The study uses confirmatory factor analysis for a model comprising seven marketing stimuli (product, price, place, promotion, people, physical evidence, and process) which influence the choice of private colleges in Yogyakarta and Central Java. Regression analysis model is used to determine the influence of marketing stimuli to the choice of private colleges. Data are gathered through survey to applicants (potential customer) from Yogyakarta and Central Java high schools. This research provides a systematic model to develop a concept of private higher education services in Yogyakarta and Central Java.